Can playing a video game foster computational thinking skills? - Zhao, Weinan; Shute, Valerie J. (Computers and education, 2019)
In this study, we evaluated the cognitive and attitudinal influences of playing a video game, Penguin Go, designed to target the development of middle school students' computational thinking (CT) skills. In addition to the overall effectiveness of the game, we investigated the impact of a specific game feature—constraints on the number of blocks in a solution. Results showed that after playing Penguin Go for less than two hours, students' CT skills improved significantly, but the additional constraints did not generate a significant impact on learning. In addition, the game overall did not influence students' attitudes toward computer science, but the constraints condition of the game negatively influenced students' attitudes toward computer science. Implications of the findings and possible directions for future research regarding using these types of games to foster computational thinking skills are discussed. •A quantitative evaluation of a video game targeting computational thinking.•Students' computational thinking skills improved significantly.•No significant impact on students' attitudes toward computer science.•Constraints on the number of blocks did not foster more learning.•Constraints on the number of blocks negatively affected students' CS attitudes.